(untitled) (Global Journal of Human-Social Science, 2024)
The shape of the Polish radio broa dcasting in the New York metropolis was largely influenced by the achievements of Poles who had been settling in this area for decades and were united by their national affiliation sense of patriotism common tradition and religion By building churches creating various institutions and media they tried to demonstrate their distinctiveness among other ethnic groups helped members of their communities and maintained Polish traditions and culture Over the decades the Polish radio broadcasting has evolved from broadcasting several-hour programs towards a professional radio broadcasting a 24-hour program It is difficult to compare Polish programs with the model that was embodied by American radio almost from the very beginning where in addition to the extensive technical infrastructure its quality was determined by a large professional staff of journalists and radio technicians Despite living abroad and the financial difficulties faced by Polish radio creators they played a significant role for their own ethnic group in the United States They played an important role in maintaining the national identity of Poles living in exile in America Keywords polish ethnic group in the United States New York emigration radio radio for the polish ethnic group journalistic genres technological changes internet radio